PROBLEMATIKA PENANGANAN KEKERASAN DALAM RUMAH TANGGA DALAM HUKUM ISLAM DAN HUKUM POSITIF - Edi Susilo; A. Kumedi Ja’far; Aulia Azhar (Nizham Journal of Islamic Studies, 2021)
This article discusses the problems of handling domestic violence according to Islamic law and positive law, the occurrence of domestic violence because many parties do not understand the handling of domestic violence both according to Islamic law and positive law. The purpose of this paper is to provide insight into the handling of domestic violence from the perspective of Islamic law and positive law, considering that previous articles have not comprehensively discussed the handling of domestic violence. The method in this research is library research, collecting data from books, journals and other library materials that discuss domestic violence. The results of this study are that in positive law there are differences between the Criminal Procedure Code and Law 23 of 2004. The Criminal Procedure Code prioritizes the perpetrators to be investigated immediately, while Law 23 of 2004 emphasizes victim services first to get protection as victims of violence. Meanwhile, according to Islamic law, sanctions or punishments are given, according to the type of crime committed. However, if the victim forgives and tends to make peace, it is permissible under Islamic law